Foreign aid, institutional quality, and income inequality in Africa: A dynamic panel threshold approach - Dalmar, Mohamed Saney; Ishak, Suryati; Ibrahim, Saifuzzaman; Hamzah, Hanny Zurina (Asian Economic and Social Society, 2024)
This study examines the impact of foreign aid and institutions on income inequality in 23 African countries during the period from 2005 to 2017. The study used a newly proposed novel dynamic panel threshold technique. The results of the study found an institutional quality threshold value of 1.622. Below the threshold, foreign aid was found to positively and significantly influence income inequality. However, above the threshold, the coefficient of foreign aid was negative with statistical significance. This implies that foreign aid tends to diminish income inequality in the presence of quality institutions. The study also used the quantile regression method to check for robustness. It showed that the conclusion between aid and inequality is the same in most of the quantiles (0.1 and 0.2). The findings can be worthwhile for sketching proper aid policies to lessen inequality. Policymakers in Africa should prioritize establishing high-quality institutions and developing measures to improve existing ones. Thus, aid could potentially reduce income inequality. This study suggests that it is important to note that aid programs can be effective when tailored to the particular needs and circumstances of each beneficiary country, as one-size-fits-all methods may not produce the anticipated outcomes. © 2024 Asian Economic and Social Society. All rights reserved.